Pengaruh Locus of Control, Kinerja Auditor dan Etika Profesi terhadap Perilaku Disfungsional Auditor: Studi Empiris pada KAP di Kota Padang - Dwika Fitria Wulandari; Erinos NR (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the influence of external locus of control, internal locus of control, auditor performance and professional ethics on auditor dysfunctional behavior. The population in this study were all public accounting firms in the city of Padang, using the total sampling method. There were 7 public accounting firms that could be used us research samples and 44 questionnaires were collected. The data analysis method used in this research is multiple linear regression. The result of this study show that external locus of control has a positive effect on auditor dysfunctional behavior, while internal locus of control, auditor performance and professional ethics have a negative effect on auditor dysfunctional behavior.